The Role of Community Participation in the Optimizing Education Services Quality: A Case Study of SMP IT Darul Fikri North Bengkulu - Sa’adah, Nairi (PPSDP International Journal of Education, 2026)
Early marriage remains a critical barrier to adolescent development, with consequences extending beyond immediate health concerns to educational attainment, professional development, and long-term human resource quality. This study systematically synthesizes evidence on how early marriage affects educational continuity, professional skill development, and economic independence, and examines its implications for human resource development. A systematic literature review (SLR) was conducted following PRISMA guidelines, with literature retrieved from Scopus, ProQuest, and Google Scholar. Studies were selected through identification, screening, eligibility assessment, and inclusion based on predefined criteria. Thematic content analysis synthesized evidence from 12 eligible studies. The findings reveal four interrelated pathways: (1) early marriage disrupts educational continuity and increases school dropout risk; (2) educational disruption limits professional and vocational skill development, creating a skills gap; (3) limited qualifications restrict career opportunities and increase economic dependency; and (4) these consequences cumulatively constrain human resource quality. Economic pressure, cultural norms, parental influence, limited educational access, and unintended pregnancy were identified as recurring contributing factors. The review demonstrates that early marriage consequences constitute an interconnected developmental trajectory from educational discontinuity to reduced human resource potential. These findings highlight the need for integrated interventions combining early-marriage prevention with educational retention, vocational development, career preparation, and economic empowerment.